EXPLORING THE POSSIBILITIES OF STRATIFICATION TECHNOLOGY IN THE TEACHING OF HIGHER MATHEMATICS (American Journal of Technology and Applied Sciences, 2024)
The integration of technology in education has revolutionized traditional teaching methods, offering new avenues for enhancing student engagement and understanding. This article explores the possibilities of utilizing stratification technology in the teaching of higher mathematics. Stratification technology refers to the implementation of layered and structured learning experiences that cater to diverse student needs and promote personalized instruction. By leveraging the capabilities of technology, educators can create dynamic and interactive learning environments that foster conceptual understanding, critical thinking, and problem-solving skills. This article examines the theoretical foundations, benefits, and strategies associated with the use of stratification technology in higher mathematics education. Furthermore, it discusses potential challenges and offers recommendations for effective implementation. Overall, the article highlights the potential of stratification technology to transform and elevate the teaching and learning of higher mathematics.